Plankton Dreams: What I Learned in Special-Ed - Rajarshi Mukhopadhyay, Tito (Immediations, 2015)
In Plankton Dreams,Tito Rajarshi Mukhopadhyay crafts a proud, satiric style: the special ed student as literary troublemaker. 'Mother had always taught me to learn from circumstance,' he writes. 'Here, the circumstance was humiliation, a particularly instructive teacher.' 'But I'm not complaining,' he continues. 'Humiliation, after all, made me a philosopher.' For all of its comic effects, the book alerts readers to an alternative understanding of autism, an understanding that autistics themselves have been promoting for years. Frustrated by how most scientists investigate autism, Mukhopadhyay decides to investigate neurotypicality, treating his research subjects the way he himself was treated. Why shouldn't the autist study the neurotypical? This artful parody of scientific endeavor salvages dignity from a dark place. It also reveals a very talented writer. It is most certainly time to study the neurotypical-his or her relentless assumptions. Perhaps by doing so we may devise a more humble and hospitable society.